The stake of informing patients of the risk of hypofertility after chemotherapy for breast cancer - Florian Martinet-Kosinski; Sébastien Lamy; Sébastien Lamy; Sébastien Lamy; Eric Bauvin; Eric Bauvin; Florence Dalenc; Charlotte Vaysse; Pascale Grosclaude; Pascale Grosclaude; Pascale Grosclaude (Frontiers Media S.A., 2023)
IntroductionToo few women with invasive breast cancer are informed of the risk of hypofertility after chemotherapy. However, this risk can be prevented by offering gamete preservation by a specialized team. We believe that if more women were informed about gamete preservation, more of them would accept it.ObjectivesThe primary objective is to describe each step of the oncofertility care pathway from provision of information to gamete preservation. The secondary objective is to estimate the impact of not receiving information by determining the proportion of women who would have undergone gamete preservation if they had been informed.Method575 women aged 18-40 years treated with chemotherapy for breast cancer between 2012 and 2017 in the Ouest-Occitanie region (~3 million inhabitants) were included. We first constructed a multivariate predictive model to determine the parameters influencing the uptake of the offer of gamete preservation among women who were informed and then applied it to the population of uninformed women.ResultsOnly 39% of women were informed of the risks of hypofertility related to chemotherapy and 11% ultimately received gamete preservation. If all had been informed of the risk, our model predicted an increase in gamete preservation of 15.35% in the youngest women (<30 years), 22.88% in women aged between 30 and 35 years and zero in those aged ≥36 years. We did not find any association with the European Deprivation Index (EDI).ConclusionOncologists should be aware of the need to inform patients aged ≤ 35 years about gamete preservation. If all received such information, the impact in terms of gamete preservation would likely be major.